2017
DOI: 10.1515/ijnes-2017-0049
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives from Academic Leaders of the Nursing Faculty Shortage in Canada

Abstract: There is a world-wide shortage of nursing faculty, which is complicated by the need for French, English, and bilingual professors in Canada. The purpose of this qualitative study was to explore the current status and effects of the nursing faculty shortage on Canadian Schools of Nursing (SON) from a leadership perspective. We conducted semi-structured interviews with 12 Deans and Directors of Canadian Schools of Nursing. The participants spoke about the faculty shortage in terms of demand, supply, and strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Another 211 articles were excluded following that review and, in the end, 9 peer-reviewed journal articles were included in this study for data extraction and analysis. Of the 9 reviewed studies, three were qualitative studies (e.g., Kirkham, 2016;Tourangeau et al, 2012;Vandyk et al, 2017), two quantitative studies (e.g., Tourangeau et al, 2014;, and four mixed-method studies (e.g., Cash et al, 2009;Singh et al, 2014;. Most of the empirical studies were small-scale, using qualitative methodologies (n = 4-12)photovoice, focus groups, interviews and narrative approaches.…”
Section: Study Search and Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another 211 articles were excluded following that review and, in the end, 9 peer-reviewed journal articles were included in this study for data extraction and analysis. Of the 9 reviewed studies, three were qualitative studies (e.g., Kirkham, 2016;Tourangeau et al, 2012;Vandyk et al, 2017), two quantitative studies (e.g., Tourangeau et al, 2014;, and four mixed-method studies (e.g., Cash et al, 2009;Singh et al, 2014;. Most of the empirical studies were small-scale, using qualitative methodologies (n = 4-12)photovoice, focus groups, interviews and narrative approaches.…”
Section: Study Search and Selectionmentioning
confidence: 99%
“…The issue of supply versus demand was frequently reported in the articles. According to Vandyk et al (2017), there are limited numbers of qualified PhD-prepared faculty available to fill their positions resulting in many unoccupied full-time faculty positions. The immediate and long-term implications of the aging nursing workforce and imminent/impending retirement of senior faculty members creates a demand for qualified applicants.…”
Section: Theme 1-supply Versus Demand (Recruitment and Hiring Practices)mentioning
confidence: 99%
See 1 more Smart Citation
“…[16,18] Gaberson, Oermann, and Shellenbarger [45] affirm that because CIs are involved to varying degrees with the curriculum, they can carefully select clinical activities that best meet the students' learning needs and which are consistent with the course goals and objectives. However, with the current shortage of faculty, nursing programs are increasingly relying on sessional or part-time CIs who may lack experience as educators, [46,47] or clinical staff who may not know the students or have little experience in guiding students, thus requiring ongoing education, support and development. [46,48,49] Similarly, participants in this study reported a lack of formal preparation and orientation to their teaching role.…”
Section: Strengths Of the Traditional Modelmentioning
confidence: 99%
“…The shortage in nursing academia continues to be a major issue that affects the capacity of nursing programs to educate and support the next generation of nurses. [1][2][3] The implementation of mentoring programs has been identified as one of the ways to possibly prevent the high rates of premature departure of faculty members just entering the new role of academic leaders, as well as to reduce faculty turnover. [4][5][6][7] Indeed, promoting teamwork and limiting isolation by bringing together new faculty members into the existing faculty group with a faculty mentorship program prevents frustration and work dissatisfaction, amongst other things.…”
Section: Introductionmentioning
confidence: 99%